Effects of Live Load on Seismic Response of Bridges: A Preliminary Study - Wibowo, H.; Sanford, D.M.; Buckle, I.G.; Sanders, D.H. (Institute of Research and Community Outreach - Petra Christian University, 2012)
Although live load is well known to have a dynamic effect on bridge response in addition to its self-weight, the significance of these effects on seismic response is unclear. In addition, most bridge design specifications have few requirements concerning the inclusion of live load in their seismic design provisions. The main objective of this study is therefore to investigate and obtain insight into the effect of vehicle-bridge interaction during earthquake shaking. The study consists of both experimental and analytical investigations. This paper focuses on the experimental work, which includes shake table testing of a 2/5-scale model of a horizontally curved steel girder bridge loaded with a series of representative vehicles. Preliminary experimental results show that the presence of the live load had a clear beneficial effect on performance for small amplitude motions, but that this improvement diminished with increasing amplitude of shaking. Parameters used to measure performance include column displacements, abutment shear forces, abutment uplift, and concrete spalling.